Six sigma optimization of multiple machining characteristics in hard turning under dry, flood, MQL and solid lubrication. (2020) - Mia, Mozammel; Gupta, Munish Kumar; Pruncu, Catalin Iulian; ,; Sen, Binayak; Khan, Aqib Mashood; Jamil, Muhammad; Faraz, Shafiul; Asef, Fahim; Imran, G.M. Shah; Rahman, M. Azizur
No abstract available